EVALUATION OF INHOMOGENEITIES IN HISTOLOGICAL STRUCTURES (CARTILAGE, RETINA) - Muche, Lutz; Rother, Paul; Friesenegger, Antje; Geupel, Markus (Image Analysis and Stereology, 2011)
This paper investigates histological tissues by means of image analysis and spatial statistics. For the quantification of cell frequencies and accumulations two statistical characteristics, intensity function and cluster density, are suggested. The samples are histological sections of human articular cartilage and human retina considered in view of changes during the ageing process. The articular cartilage is characterized by continuous changes of both functions, the cell intensity as well as the clusterization. In contrast, the retina is a trilaminar structure formed in the early embryonic stage without changes by ageing.